Beyond the perpetrator: tackling the varied underpinnings of domestic violence on the Tibetan plateau - Rajan, H (2017)
This thesis explores domestic violence (DV) on the northeastern edge of the Tibetan plateau, in Qinghai province of the People’s Republic of China (PRC). (See Appendix 1 for maps of the study region.) It is based on fifteen months of fieldwork conducted in 2012 and 2013, and upon interviews with 100 women and men, participant observation, and a reading of local proverbs, song, and popular literature. As this is a thesis by publications, three stand-alone articles dealing with selected aspects of domestic violence (DV) in the study region, plus two articles dealing with social phenomena closely related to DV, are included in the subsequent pages...